1995
DOI: 10.1177/016224399502000105
|View full text |Cite
|
Sign up to set email alerts
|

Toward a More Democratic Ethic of Technological Governance

Abstract: Recent scholarship in technology and society studies has given attention to the notion of technological citizenship. This article seeks to further integrate perspectives on this topic with theoretical contributions about the development of moral autonomy. The author challenges the presumption that the strategy of expanding opportunities for participation in technological decision making will in itself develop people's autonomy and citizenship. He argues that concurrent efforts must be made to democratize the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Experts have the education, skills, and time to devote to policy concerns. In contrast, citizens lack the special training and resources needed to be cogent about complex policy problems, especially those involving highly sophisticated technology (Aron, 1979;Cohen, 1995;DeSario & Langton, 1984;Hadden, 1981;Morgan, 1984;Zimmerman, 1995). As a consequence of these disparities, professionals and experts gain in power, while citizens, unable to participate as coequals, decrease their involvement.…”
Section: Arenas Of Direct Citizen Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Experts have the education, skills, and time to devote to policy concerns. In contrast, citizens lack the special training and resources needed to be cogent about complex policy problems, especially those involving highly sophisticated technology (Aron, 1979;Cohen, 1995;DeSario & Langton, 1984;Hadden, 1981;Morgan, 1984;Zimmerman, 1995). As a consequence of these disparities, professionals and experts gain in power, while citizens, unable to participate as coequals, decrease their involvement.…”
Section: Arenas Of Direct Citizen Participationmentioning
confidence: 99%
“…The following articles offer a sample of some of the cases: Ireland (1975), Kauffman and Shorett (1977), Godschalk and Stiftel (1981), Plumlee, Starling, and Kramer (1985), Kraft and Kraut (1985), and Desai (1989). For those focusing on the tensions between the democratic ethic and technology, see Fiorino (1990), Frankenfeld (1992), Laird (1993), Zimmerman (1995), and Abel and Stephan (2000).…”
Section: Next Stepsmentioning
confidence: 99%
“…-Technology governance: This parameter highlights the importance of transparency, participation and emancipation in making technological choices (Zimmerman, 1995), especially by public entities. Choices for a particular technology or platform (e.g.…”
Section: Business Model Frameworkmentioning
confidence: 99%
“…(47) (Maass 2003) This trend is a public good in that it reduces pressures on the public purse, but it also raises questions about the relationship between 'free inquiry' and the 'free market' (Fuller 2000). At an ethical level it also raises questions about public control of the research agenda, Zimmerman (1995) identified a general trend of shifting a central governance function from the political realm to industry or in his terms 'some of the most significant and powerful institutions of our time'(86). In these terms the justification for extended exclusive licenses (time limited monopolies) for certain drugs that have very high public good utility is not at all proven.…”
Section: Conversely It Is Clear From the Oecd Report Funding Of Publimentioning
confidence: 99%